Hamburgische Dramaturgie - Lessing, Gotthold Ephraim 1729-1781; Träger, Claus 1927-2005 (Stuttgart Reclam, 1972)
'The Hamburg Dramaturgy' is a highly influential work on drama by Gotthold Ephraim Lessing, written between 1767 and 1769 when he worked as a dramaturg for Abel Seyler's Hamburg National Theatre.[1] It was not originally conceived as a unified and systematical book, but rather as series of essays on the theater, which Lessing wrote as commentary on the plays of the short-lived Hamburg National Theater. This collection of 101 short essays represents one of the first sustained critical engagements with the potential of theater as a vehicle for the advancement of humanistic discourse. In many ways, the Hamburg Dramaturgy defined the new field of dramaturgy, and also introduced the term.
Gotthold Ephraim Lessing (1729-1781) was a German writer, philosopher, dramatist, publicist and art critic, and a representative of the Enlightenment era. His plays and theoretical writings substantially influenced the development of German literature. He is widely considered by theatre historians to be the first dramaturg in his role at Abel Seyler's Hamburg National Theatre.
Keywords: 18th Century (1701-1800); 20th Century (1901-2000); Theater criticism; Hamburg (Germany)